2018
DOI: 10.3892/mmr.2018.9432
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of multi Ewing sarcoma microarray datasets identifies several prognosis biomarkers

Abstract: Ewing sarcoma (ES) is a common primary malignancy in children and adolescents. Progression of treatment methods hasn't contributed a lot to the imrovement of prognosis. To identify potential prognostic biomarkers, a meta-analysis pipeline of multi-gene expression datasets for ES from the Gene Expression Omnibus (GEO) was performed. Three datasets were screened and differential expression genes (DEGs) in ES samples compared with normal tissues were identified through limma package and subjected to network analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…A low tumor mutational burden (TMB) is a general feature of sarcomas and other pediatric cancers. In our cohort, all patients had low TMB (< 10 mut/Mb), consistently with previous studies [ 14 , 18 , 24 ]. In other studies, relapsed tumors showed a 2- to 3-fold increased number of mutations [ 25 ]; however, probably due to a low number of relapsed/metastatic cases, we did not confirm this observation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A low tumor mutational burden (TMB) is a general feature of sarcomas and other pediatric cancers. In our cohort, all patients had low TMB (< 10 mut/Mb), consistently with previous studies [ 14 , 18 , 24 ]. In other studies, relapsed tumors showed a 2- to 3-fold increased number of mutations [ 25 ]; however, probably due to a low number of relapsed/metastatic cases, we did not confirm this observation.…”
Section: Discussionsupporting
confidence: 92%
“…This is due to the oncogenic driving translocation between the EWSR1 gene and ETS family transcription factors that dominated the ES genetic landscape [11]. The most common fusion is EWSR1-FLI, observed in 80-85%, followed by EWSR1-ERG fusion [11,[14][15][16]. Besides characteristic fusion, additional pathogenic point mutations are observed in numerous genes, with the most common loss-offunction mutations in STAG2, TP53, and CDKN2A genes.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of data by Yin et al found that PYGM , MEF2C , and TRIM63 were also downregulated, and their expression was positively associated with survival rates in ES [33] . However, BUB1B (a member of spindle assembly checkpoint protein) and RACGAP1 (a component of central spindle and essential for cytokinesis induction), both upregulated in ES, were negatively associated with survival rates of ES.…”
Section: Resultsmentioning
confidence: 99%
“…ES is one of a few tumors that display profound PAS+ staining during histopathological analyses, demonstrated to be glycogen through an additional step of diastase treatment (Schajowicz, 1959; Telles et al , 1978). In fact, glycogen metabolic enzymes are drastically altered by EWS‐FLI1 (Tanner et al , 2017; Aynaud et al , 2020), including the glycogen phosphorylase muscle isoform ( PYGM ; Yin et al , 2018). The MALDI‐MSI method confirms extensive glycogen accumulation in ES tumors.…”
Section: Discussionmentioning
confidence: 99%